The humanity archive : recovering the soul of Black history from a whitewashed American myth - Fowler, Jermaine (Storyteller) (Row House, 2022)
"Using history as a foundation, The Humanity Archive uses storytelling techniques to make history come alive and uncover the truth behind America's whitewashed history. Challenging dominant perspectives, author Jermaine Fowler goes outside the textbooks to find recognizably human stories. Connecting current issues with the heroic struggles of those who have come before us, Fowler brings hidden history to light"--Provided by publisher.